PRE EKLAMPSIA TERHADAP BERAT BADAN LAHIR BAYI ( Studi di RSUD Dr. Soegiri di Lamongan) - Lukman Hakim Hidayatullah,; . Muarrofah; . Baderi (Jurnal Keperawatan, 2014)
Preeclampsia is hypertensions’ growth accompanied proteinuria and edema after age of pregnancy 20weeks. Study before at 20-27 March 2014 gained that 10 preeclampsia mothers have born baby with normalof weight body. There 7 and 3 babies with BBLR. This research is to analyze relation preeclampsia to babybirth weight body in RSUD Dr. Soegiri in Lamongan.Cross Sectional with using Retrospective. Population of all patient in RSUD Dr. Soegiri in Lamongan asmany as 50 persons with 44 sample of respondents. Gaining technique of sample by using Simple RandomSampling. The variable is preeclampsia to baby birth weight body. Instrument of this research usesobservation and analyzing data and tabulation and the test use Chi Square test α=0,05 with SPSS 17.00Result of this research can be gained that almost preeclampsia to baby birth weight body is lightpreeclampsia as many as 37 respondents (84,1%) and heavy preeclampsia as many as 7 respondents(15,9%). Most of the light preeclampsia with normal BBL as many as 20 respondents (45,5%) analyzing ChiSquare test p < 0,008.Conclusion p ≤ α there is relation between preeclampsia with baby birth weight body in RSUD Dr. Soegiri inLamonganWith this result of research, so hoped that medical staff can give counseling to pregnant mother to keepmanagement of eating, and check up the pregnancy routinely to hospital so mother can birth baby withnormal baby birth weight bodyKey Words : Preeclampsia, Baby Birth Weight Body, Low Baby Birth Weight Body